842The effect of post TAVR pacemaker implantation on mid and long-term mortality. (18th June 2020) - Hochsatdt, A; Merdler, I; Meridor, Y; Schwartz, A L; Steinvil, A; Finkelstein, A; Viskin, S; Rosso, R
Abstract: Introduction: Transcatheter aortic valve replacement (TAVR) is standard of care for patients with symptomatic severe aortic stenosis at high risk for surgery. Atrioventricular conduction defects remain a frequent complication of the procedure, and permanent pacemaker (PPM) implantation has been associated with increased long-term mortality in some studies. Purpose: We evaluated the influence of PPM on mid and long-term mortality in a very large cohort of patients undergoing TAVR. Methods: All patients undergoing TAVR in one tertiary cardiac catheterization center were included. Patients were categorized into three groups: 1) patients with a PPM implantation prior to the procedure, 2) patients with post procedural PPM implantation and 3) patients without PPM. Univariate and multivariate comparisons was preformed for all-cause mortality for up to 6 years. Sub-analyses were preformed according to ventricular pacing burden on outcome. Results: A cohort of 1, 306 post TAVR patients were followed for a median period of 38 [IQR 20-58] months. Risk factors associated with need for post procedural PPM implantation were male gender, dialysis treatment, NYHA ≥3 and pre procedural RBBB (p < 0.03 for all). Univariate mid-term (up to 12 months) and long-term (up to 72 months) mortality were similar for patients regardless of post procedural PPM (p = 0.361 and p = 0.287 accordingly), yet long term mortality was significantly higher in the pre-TAVR PPM group (OR 1.6, p < 0.001). Multivariate analysis of mortality by PPM group and patients" clinical characteristics did not show any independent mid or long-term survival effects of PPM either prior to or after the procedure (p = 0.974 and p = 0.300 accordingly). Sub-analysis of the cohort according to average right ventricular pacing percent, showed no significant mid-term or long-term mortality difference between patients having high (>90%), moderate (40-90%), mild (mild 40-10%) and minimal (<10%) pacing burden (p > 0.320 for all comparisons). Analysis of patients with high pacing burden vs. non-paced patients showed similar mortality trends for both mid and long-term mortality (p = 0.537 and p = 0.127 accordingly). Conclusion: This long-term cohort of consecutive patients undergoing TAVR showed that post procedure PPM was not associated with increased long-term mortality. This conclusion was not altered by ventricular pacing burden.